(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Over the Counter (OTC) Medicines usage for common ailments like fever, cough cold or gastro intestinal complaintshave been common in Indian setting and also increasing in other countries as well. Although these medications can be effective, cancause adverse effects especially in paediatric age group if administered in improper dosage or method. This study is an attempt toidentify the parental beliefs and methods regarding usage of OTC drugs in their children.Aim: To identify parental perceptions, knowledge, applications and practice of using OTC drugs in their children.Materials and Methods: This cross-sectional questionnaire-based study was conducted at Saveetha Medical College Hospital, Chennai,Tamil Nadu, India (tertiary care centre) from May 2022 to September 2022. Parents of children aged up to 14 years were subjected toa validated questionnaire; respondents mostly being mothers. The questionnaire had 3 parts with questions pertaining to socio –demographic details (part 1), knowledge application and practice of using OTC drugs and impact of the covid – 19 pandemic on parentsseeking healthcare for their children. The data was tabulated onto excel sheets and analysed using SPSS software for windows.Results: A total of 83 children participated in the study. Majority of the study population was greater than 1 year. Upon analysing theresponses, 74 (89%) of the respondents had OTC drugs at home with most common being drugs for fever (51.4%) followed by coughand cold (33.8%), with the major source of OTC drugs being the nearby pharmacy (97.3%) which was statistically significant amongsteducated mothers purchasing OTC medications with a p value of 0.05. Parents did not have much knowledge about the side effects orhow the drugs work. With the outlook of visiting a hospital, 50% of the parents still felt it is necessary to visit a hospital for theirchildren’s illness. Among those who were apprehensive to visit a hospital, the primary concern was fear of infection in case they visiteda hospital which was statistically significant with a p value of 0.001. Overall, parents felt that despite OTC drugs, it is the treatment ofa doctor that plays a role in the overall recovery of their child.Conclusion: This study showed majority of the parents have OTC drugs in their home and use self-medication to treat illness in theirchildren. However, knowledge and awareness in regarding drug dosage, adverse effects and drug actions was found to be less evenamongst educated parents. Parental education during hospital visits by treating doctors and information on the drug labels will help theparents to use these medications as a temporary measure until their child meets the doctor and also help to avoid any possible adverseeffects due to improper OTC drug administration.